Development and Validation of a Multiresidue Method for Fluazifop‐p–butyl and Its Two Major Relevant Metabolites in Panax ginseng Using a Modified QuEChERS Method and HPLC‐ESI‐MS/MS. Issue 19 (22nd May 2019) - Li, Guangling; Hou, Zhiguang; Lu, Zhongbin; Chen, Xiling
Abstract: Fluazifop‐ p ‐butyl (FPB) is used to control the gramineous weeds in Panax ginseng field, which has the risk of exceeding the maximum residue limit of FPB in Panax ginseng . A modified QuEChERS sample preparation method was developed for the simultaneous determination of FPB and its two major relevant metabolites, fluazifop‐ p ‐acid (FP) and 2‐hydroxy‐5‐ trifluoromethylpyridin (TFMP) in Panax ginseng by using Carboxylated multi‐walled carbon nanotubes (MWCNTs‐COOH) mixed with ostade‐cylsilane (C18 ), primary secondary amine (PSA), and graphitized carbon black (GCB) as purification materials. Furthermore, the HPLC‐MS/MS parameters were optimized. The method was further validated by determining the linearity (R 2 >0.999), fortified recovery (77.6‐97.8%), relative standard deviation (<13.6%) and sensitivity (LOQ, 2.0‐ 8.6 μg kg‐1 for FPB, 3.9‐5.8 μg kg −1 for FP and 3.5‐9.0 μg kg −1 for TFMP in Panax ginseng root, leaf, and seed samples, respectively). The main advantages of the method are high recovery, high sample throughput, facile sample preparation, a smaller volume of organic solvents and low cost per sample. The entire method can withstand practice testing expected to be used for the screening of FPB residue in Panax ginseng samples. Abstract : Panax ginseng, a multipurpose herb in self‐medication either with or without pharmaceutical preparation, was a gift of God or nature. How can Panax ginseng which was known as the "King of Herbs" be associated with the common herbicide Fluazifop‐ p ‐butyl? This study proposed a very promising multiresidue method for Fluazifop‐ p ‐butyl and its two major relevant metabolites in Panax ginseng samples using a modified QuEChERS method and HPLC‐ESI‐MS/MS.